The Development Strategy of the Sultanate Palace as a Heritage Tourism Attraction in Sumbawa Besar City, West Nusa Tenggara Province - Dova Novita, Dova Novita; I Putu Anom, I Putu Anom; Yayu Indrawati, Yayu Indrawati (International Journal of Technology and Education Research, 2025)
The Sultanate Palace, located in Sumbawa Besar City, West Nusa Tenggara Province, has high historical and cultural value, symbolizing the civilization of the Sumbawa people, especially in the field of government, and serving as historical evidence of the glory of the Sumbawa Sultanate in the past. However, the management and development of the palace as a cultural heritage tourist attraction has not been optimal. Therefore, this study aims to formulate a development strategy by analyzing the current condition of the Sultanate Palace using the TALC approach and 4A components, as well as pentahelix collaboration. This study uses a descriptive qualitative approach with data collection techniques including interviews, observation, and documents, which are then analyzed using SWOT and PESTEL analysis. The results of this study indicate that the Sultanate Palace is still in the involvement stage, and although pentahelix collaboration has been formed informally, it is still dominated by the government and cultural figures. The proposed development strategies include periodic attraction innovations, Sumbawa cultural workshops, heritage building preservation and conservation tours, gallery exhibitions and workshops, comparative studies with neighboring destinations, community involvement, brand strengthening, human resource capacity development, packaging traditional games and storytelling, and private sector involvement through CSR programs.